First Report of Congenital Short Bowel Syndrome in an Iranian Patient Caused by a Mutation in the CLMP Gene - Gharesouran, Jalal; Esfahani, Behnaz Salek; Valilou, Saeed Farajzadeh; Moradi, Mohsen; Mousavi, Mir Hadi; Rezazadeh, Maryam (Journal of Pediatric Genetics, 2019)
Congenital short bowel syndrome (CSBS) is a rare congenital neonatal disorder. CSBS results from intestinal impairment during embryogenesis. Mutated CXADR-like membrane protein (CLMP) and Filamin A genes are involved in the cause of CSBS. In this study, due to our misdiagnosis, we had to perform whole exome sequencing on the patient, and also we implemented cosegregation analysis on his parents with consanguineous marriage and also parents' mothers. We identified a homozygous loss of function mutation in the CLMP gene in exon 5 (c.664C > T, p.R222X). Also, both parents and grandmothers of the proband were heterozygous for this mutation. Loss of function mutation in CLMP causes CSBS, leading to impaired intestinal development.
Keywords: congenital short bowel syndrome; CXADR-like membrane protein; whole exome sequencing